Religiosity Dan Personal Norm Pengaruhnya Terhadap Keputusan Pembelian Produk Halal: Mediasi Sikap Konsumen - Aritama, Fauzaan Dhiemas; Ariwibowo, Fajar; Purwantiningsih, Dewi; Wahyana, MS Agung; Amri, Sholiqul; Wulandari, Fitri (Jurnal Ilmiah Ekonomi Islam, 2023)
The purpose of this research is to see how the influence of personal norms and religiosity on the decision to purchase halal products through attitude as an intervening variable in Surakarta. Four variables used are personal norms, religiosity, attitudes, and purchase decisions. This research used quantitative research using a sample of 143 respondents who had purchased various types of halal products in Surakarta using the non-probability sampling method, namely purposive sampling, which was then analyzed using SPSS. The analysis technique used in this study uses multiple linear regression analysis to determine the direct impact, and uses path analysis to determine the indirect effect or through intervening variables. The findings of this study found that personal norms and religiosity had a positive and significant influence on attitudes, then attitudes did not have a positive and significant effect on purchasing decisions, and personal norms did not have a positive and significant effect on purchase decisions. But, religiosity had a positive and significant impact on purchase decisions. The mediating role of attitude has no positive or significant effect on the relationship between personal norms and religiosity on purchase decisions for halal products.